Ensemble estimates of global wetland methane emissions over 2000–2020 - Z. Zhang; B. Poulter; J. R. Melton; W. J. Riley; G. H. Allen; D. J. Beerling; P. Bousquet; J. G. Canadell; E. Fluet-Chouinard; P. Ciais; N. Gedney; P. O. Hopcroft; et al. (Biogeosciences)
Due to ongoing climate change, methane (CH4) emissions from vegetated wetlands are projected to increase during the 21st century, challenging climate mitigation efforts aimed at limiting global warming. However, despite reports of rising emission trends, a comprehensive evaluation and attribution of recent changes remains limited. Here we assessed global wetland CH4 emissions from 2000–2020 based on an ensemble of 16 process-based wetland models. Our results estimated global average wetland CH4 emissions at 158 ± 24 (mean ± 1σ) Tg CH4 yr−1 over a total annual average wetland area of 8.0 ± 2.0×106 km2 for the period 2010–2020, with an average increase of 6–7 Tg CH4 yr−1 in 2010–2019 compared to the average for 2000–2009. The increases in the four latitudinal bands of 90–30° S, 30° S–30° N, 30–60° N, and 60–90° N were 0.1–0.2, 3.6–3.7, 1.8–2.4, and 0.6–0.8 Tg CH4 yr−1, respectively, over the 2 decades. The modeled CH4 sensitivities to temperature show reasonable consistency with eddy-covariance-based measurements from 34 sites. Rising temperature was the primary driver of the increase, while precipitation and rising atmospheric CO2 concentrations played secondary roles with high levels of uncertainty. These modeled results suggest that climate change is driving increased wetland CH4 emissions and that direct and sustained measurements are needed to monitor developments.